Fine Tuning of Phosphorothioate Inclusion in 2′-O-Methyl Oligonucleotides Contributes to Specific Cell Targeting for Splice-Switching Modulation - Aoki, Yoshitsugu; Rocha, Cristina S. J.; Lehto, Taavi; Miyatake, Shouta; Johansson, Henrik; Hashimoto, Yasumasa; Nordin, Joel Z.; Mager, Imre; Aoki, Misako; Graham, McClorey; Sathyaprakash, Chaitra; Roberts, Thomas C.; et al. (Frontiers in Physiology, 2021)
Splice-switching antisense oligonucleotide (SSO)-mediated correction of pre-mRNA transcripts containing frame-disrupting mutations by exon-skipping is a highly promising treatment method for muscular diseases, such as Duchenne muscular dystrophy (DMD). Phosphorothioate (PS) chemistry, a commonly used oligonucleotide modification, has been shown to increase stability and improve the pharmacokinetics of SSOs. However, PS inclusion in 2’-O-Methyl SSOs (2OMe) on cellular uptake and splice switching is less well understood. Here, we demonstrate that PS modification facilitates the uptake of 2OMe in H2k-mdx myoblasts. Furthermore, we found that nuclear accumulation of SSOs and high splice-switching activity depends on PS inclusion in 2OMe (2OMePS), as tested in various reporter cell lines carrying pLuc/705. Increased exon-inclusion activity was observed in muscle, neuron, liver and bone cell lineages via both gymnotic uptake and lipofection of 2OMePS. Using photoactivatable-ribonucleoside-enhanced crosslinking and a subsequent proteomic approach, we identified several 2OMePS-binding proteins likely to play a role in the trafficking of 2OMePS to the nucleus. Ablation of Ncl by siRNA enhanced 2OMePS uptake in C2C12 myoblasts and upregulated luciferase RNA splicing in the HeLa Luc/705 reporter cell line. Overall, we demonstrate that PS inclusion increases nuclear delivery and splice switching in muscle, neuron, liver and bone cell lineages and that modulation of 2OMePS binding partners may improve SSO delivery.